2016
DOI: 10.1111/zph.12253
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Wild Canids in the Epidemiology of Rabies in Northeast Brazil: A Retrospective Study

Abstract: Rabies is an endemic disease in Brazil, where it is considered a serious public health problem. Although the number of human and dog-transmitted cases has declined in recent decades, rabies in wildlife has emerged considerably. Among the sylvatic animals, wild canids have been considered important hosts of the rabies virus. We performed a retrospective study of reported cases of rabies in wild canids and human victims in Ceará state (Northeast Brazil) during 2003 to 2013. Information was provided by government… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
1
19
0
1
Order By: Relevance
“…The findings reported here are in agreement with previous studies performed in different biomes in Brazil, which demonstrated that wild animals have been exposed to RABV as indicated by detection of RABV antigens or RVNA identification (Antunes et al, ; Araujo et al, ; Cordeiro et al, ; Jorge et al, ; Rocha et al, ). In Brazil, from 2002 to 2012, the number of laboratorial confirmed cases of rabies, by direct fluorescent antibody test (DFAT) in terrestrial wild animals was 460 (Rocha et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings reported here are in agreement with previous studies performed in different biomes in Brazil, which demonstrated that wild animals have been exposed to RABV as indicated by detection of RABV antigens or RVNA identification (Antunes et al, ; Araujo et al, ; Cordeiro et al, ; Jorge et al, ; Rocha et al, ). In Brazil, from 2002 to 2012, the number of laboratorial confirmed cases of rabies, by direct fluorescent antibody test (DFAT) in terrestrial wild animals was 460 (Rocha et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…As a consequence, knowledge on rabies circulation in wild animals remains limited to reports on specific regions of the country. In the Northeast, for instance, seropositive crab-eating foxes have been frequently identified; these, occasionally, have been implicated in the transmission of RABV to domestic dogs (Carnieli et al, 2008;Cordeiro et al, 2016). Seropositive capuchin monkeys and crab-eating foxes from the biome Atlantic Forest in the State of São Paulo (Almeida, Massad, Aguiar, Martorelli, & Joppert, 2001;Antunes et al, 2017;Araujo et al, 2014;Machado et al, 2012) and from the biomes Pantanal and Cerrado in the Midwest (Jorge et al, 2010) have also been described.…”
Section: Introductionmentioning
confidence: 99%
“…Os dados epidemiológicos são essenciais tanto para os médicos, na decisão do tratamento profilático pós-exposição a ser instituído, como para os veterinários, na observação clínica e adoção de medidas relativas ao animal agressor. A vigilância epidemiológica é, portanto, fundamental para o controle da raiva 12 .…”
Section: ▄ Introduçãounclassified
“…thous ) was identified as a reservoir and transmitter of an independent genetic variant derived from the variant maintained by dogs, which has also been isolated from raccoons ( Procyon cancrivorus ) and one case in human (Carnieli et al., ; Favoretto et al., ). A large annual number of cases of aggression and post‐exposure treatments in humans and cases registered in this animal species have been reported (Cordeiro et al., ). In 2015, an epidemic of dog rabies occurred in the midwestern region of Brazil due to AgV1 that originated in Bolivia (Brazil, Ministry of Health, ), supporting the importance of collaboration between countries for the control of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%